Comparison of KingVision videolaryngoscope channelled blade with Tuoren videolaryngoscope non-channelled blade in a simulated COVID-19 intubation scenario by non-anaesthesiologists and experienced anaesthesiologists: A prospective randomised crossover mannequin study. (June 2021) - Gupta, Anju; Trikha, Anjan; Ayub, Arshad; Bhattacharjee, Sulagna; Aravindan, Ajisha; Gupta, Nishkarsh; Prakash, Kelika; Aggarwal, Richa; Ganesh, Venkata; Soni, Kapil Dev; Malhotra, Rajeev Kumar
Abstract: Purpose: A videolaryngoscope has been recommended for intubation in the COVID-19 scenario but the videolaryngoscope providing optimal intubation conditions is not ascertained. We compared KingVision channelled blade with a non-Channelled videolaryngoscope for intubation times in a simulated COVID-19 intubation scenario by both anaesthesiologists and non-anaesthesiologists. Methods: This prospective randomised cross over mannequin study was conducted in a skill training lab. 25 anaesthesiologists and 25 non-anaesthesiologists donned in standard personal protective equipment performed 100 intubations with KingVision and Tuoren videolaryngoscopes in a mannequin covered with a transparent plastic sheet. The total intubation time, percentage of glottic opening scores, first attempt success rates were assessed. Results: The mean difference in intubation times in anaesthesiologists and non-anaesthesiologist less with KingVision videolaryngoscope (21.1s; 95% CI 9.6–32.6s vs. 35.9s; 95% CI 24.4–47.4 s; P = 0.001). Percentage of glottic opening score was significantly better with KingVision by non-anaesthesiologists (60; IQR 42.5 to 75 vs. 70; IQR 50 to 100; P = 0.019). KingVision provided superior first attempt success rate in non-anaesthesiologists (84% vs. 61.9%; P = 0.02) and anaesthesiologists (96% vs. 76%; P = 0.12). Conclusion: KingVision channelled videolaryngoscope provided faster intubation times, glottic views and first attempt success rates in a simulated COVID-19 scenario in manikins and might be preferred over videolaryngoscopes with non-channelled blade. The findings need to be further verified in humans. Trial registration: ctri.nic.in identifier: REF/2020/05/033338. Highlights: Intubation in COVID-19 scenario is challenging especially in hands of non-anaesthesiologists. VL have been advocated for intubation in COVID-19 setting but specific type of VL to be used has not been ascertained yet. We compared a channelled to a non-channelled blade VL in COVID scenario with respect to improvement in intubation conditions. KingVision channelled VL reduced the intubation time and difficulty for both anaesthesiologists and non-anaesthesiologists.